2020
DOI: 10.1177/1178622119898460
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Uptake of Salty Soils by Ornamental Sunflower, Using Cow Manure and Biosolids: A Case Study in Alborz city, Iran

Abstract: Heavy metals are among the most critical environmental pollutants close to industrial areas. One example is the cultivated fields in the south of Alborz industrial city in Iran, which is irrigated by treated industrial wastewater. It is contaminated by heavy metals and irrigation with wastewater treatment plants effluent, which made it salty. In this study, the application of 2 amendments, biosolids and cow manure, in improving the heavy metal accumulation in the ornamental sunflower from these types of soils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
2
15
0
1
Order By: Relevance
“…The chi-square value also showed, there is a significant association between participation in decision-making process and their participation in SWC with the value of ( = 173.570, df = 1, P = .000, P < .05). In agreement with this result, an investigations elaborated by Yazdanbakhsh et al 4 and Ali and Kedru 47 demonstrated that indigenous soil conservation technologies such as contour plowing, manuring, crop rotation and residue, cut-off drains, and ditches are considered as an effective methods of conservation measures. Other authors also affirmed that hills, together with side terracing and check dams, were among the most frequently used physical structures for SWC.…”
Section: Resultssupporting
confidence: 57%
“…The chi-square value also showed, there is a significant association between participation in decision-making process and their participation in SWC with the value of ( = 173.570, df = 1, P = .000, P < .05). In agreement with this result, an investigations elaborated by Yazdanbakhsh et al 4 and Ali and Kedru 47 demonstrated that indigenous soil conservation technologies such as contour plowing, manuring, crop rotation and residue, cut-off drains, and ditches are considered as an effective methods of conservation measures. Other authors also affirmed that hills, together with side terracing and check dams, were among the most frequently used physical structures for SWC.…”
Section: Resultssupporting
confidence: 57%
“…The factors affecting the amounts of metal that a plant absorbs those controlled by the concentration and speciation of the metal in the soil solution; the movement of metal from the bulk soil to the root surface; the transport of the metal from the root surface into the root, and its translocation from the root to the shoot [28,29]. Plants readily uptake HMs dissolved in soil solution in ionic or chelated, or complex forms [30,31]. Several organic and inorganic agents might effectively and specifically increase HMs solubility that could be accumulated by several plant species [32].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it should be noted that land use may affect the relationships among soil variables, as discussed by other authors (e.g., [88][89][90][91]). Nonetheless, topography affects soil properties as well due to the local redistribution of water, solar radiation, and parent material through erosion and deposition processes [92][93][94].…”
Section: Resultsmentioning
confidence: 79%